Pengaruh dari Direct Field Component pada Ruang Akustik dengan menggunakan SEA Model - Munawir, Al; Darsan, Herri; Murhaban, Murhaban (Jurnal Mekanova, 2019)
Statistical Energy Analysis (SEA) is a well-known method to analyze the flow of acoustic and vibration energy in a complex structure. This study investigates the application of the corrected SEA model in a non-reverberant acoustic space where the direct  field component from the sound source dominates  the total  sound  field rather than  a diffuse field in a reverberant space which the  classical SEA model assumption is based on. A corrected SEA model is proposed where the direct ?eld component in the energy is removed and the power injected in the subsystem considers only the remaining power after the loss at ?rst re?ection.  Measurement is conducted a box divided into two rooms separated by a partition with an opening where the condition of reverberant and non-reverberant can conveniently be controlled. In the case of a non-reverberant space where acoustic material was installed inside the wall of the experimental box, the signals are corrected by eliminating the direct ?eld component in the measured impulse response. Using the corrected SEA model, comparison of the coupling loss factor (CLF) with the theory shows good agreement.